Dynamics of the Implementation of the Teams Games Tournament (TGT) Model in Developing Students’ Mathematical Critical Thinking Skills - Babul Jannah; Erma Fatmawati; Hartono Hartono (FKIP - Universitas Riau, 2026)
This study was motivated by students’ low mathematical critical thinking skills, which are often associated with teacher centered learning that limits active participation. The study aimed to describe the implementation dynamics of the Teams Games Tournament (TGT) model and explore student interaction patterns in facilitating mathematical critical thinking. A descriptive qualitative case study was conducted involving one fourth grade teacher and four students of MI Al Falahiyah Lumajang selected through purposive sampling. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and member checking. The findings showed that TGT created a collaborative learning environment through class presentations, heterogeneous teams, academic games, tournaments, and team recognition. Student interactions, including idea negotiation, strategy verification, and collaborative decision-making, promoted mathematical analysis, evaluation, and justification. In addition, post tournament reflection strengthened students’ metacognitive awareness. The study concludes that the TGT model effectively supports the active and reflective development of students’ mathematical critical thinking skills through collaborative learning experiences.